Mechanistic insight into the individual ionic transportation in polymer electrolytes for use in dye-sensitized solar cells - Wu, Congcong; Guo, Siyao; Jia, Lichao; Han, Song; Chi, Bo; Pu, Jian; Jian, Li (Royal Society of Chemistry, 2013)
Polymer electrolytes, acting as an ionic solid-state conducting phase, have been demonstrated as promising charge carrying mediators for energy storage devices. However, the large majority of polymer electrolyte studies are focused on cation transportation and little consideration has been given to the investigation of the anion transportation mechanism. In this study we focus on the individual ionic transportation mechanisms in polymer electrolytes for potential application in dye-sensitized solar cells (DSSCs). To explore the ionic transportation mechanism, polymer electrolytes with different ion concentrations were studied. The influence of ion concentration on the structure of the polymer electrolytes was elucidated using X-ray diffraction (XRD) and Raman spectroscopy. Additionally, the temperature and composition dependence of the ionic conductivity and restricted ion diffusion coefficientof the polymer electrolytes were studied to gain an insight into the ionic transportation mechanism. The behavior of the anion transportation was further discussed via the addition of I2 into the polymer electrolytes. The results imply that the disorder and flexibility of the polymer matrix are favorable for ionic transportation, and that mass transportation can be facilitated by increasing the I2 concentration in the polymer electrolyte, which could be applied in DSSCs.